Aglomerações e vantagens competitivas locacionais : uma avaliação das políticas e ações de apoio aos arranjos produtivos locais de Sergipe - Oliveira, Michele Santos (2010)
This main objective of the present dissertation is to identify and evaluate the actions and policies that support Local Productive Arrangements (APLs) in the state of Sergipe by articulating theoretical notions with primary and secondary data collected during the empirical research. The conceptual framework developed in the dissertation treats the fundamental elements of productive arrangements by identifying their key features, characteristics, associated local competitive advantages, and public policy models for the promotion of APLs. The empirical research was divided into two interdependent phases. Initially, data was collected from secondary sources such as RAIS/MTE, IBGE, SECEX/MDIC, BACEN, SEPLAN and SEDETEC. This data represented Sergipe s participation in the Northeast region and Brazil, in areas such as GDP, international exports and imports, value and share of GDP of Sergipe s territories; the number of enterprises and workers in Sergipe; regional export and import flows, APLs identified, etc. In a second phase data was collected from government entities responsible for supporting APLs. For such, a questionnaire was applied to a total of 25 institutions; additional, more detailed questionnaires were applied to those institutions that contributed most to the promotion and development of APLs in the state. The respondents were directors or managers of the institutions responsible for actions directed to productive agglomerations. The research identified and evaluated initiatives that support APLs, confirming the importance of interaction among economic, social and political actors as well as the need for implementing public policies that specifically consider known bottlenecks, such as those identified in this dissertation, for regional and local development.